Influence of relative humidity on the strength and stiffness of unstabilised earth blocks and earth masonry mortar. (1st August 2022) - Wiehle, Philipp; Simon, Sebastian; Baier, Johanna; Dennin, Luise
Graphical abstract: Highlights: The material composition of load bearing earth masonry materials depends on the application (mortar vs. block) and the manufacturing method. Earth blocks contain a higher amount of clay minerals compared to mortars. The content of clay minerals and organic matter governs the materials equilibrium moisture content. A normalisation of the compressive strength and Young's modulus by the values at standard climate conditions reveals a linear reduction of both for increasing relative humidity. The relation in good approximation can be described regardless of the material composition. Abstract: Aim of this study is to provide information about moisture dependent material behaviour of unstabilised load-bearing earth blocks and mortars. Compressive strength and Young's modulus were investigated after conditioning in varying relative humidity reaching from 40 % up to 95 %. The material composition and physical properties were investigated to understand the influence of relative humidity onto the mechanical properties. A normalisation of strength and stiffness by the values obtained at 23 °C and 50 % relative humidity reveals a linear dependence of compressive strength and Young's modulus that is regardless of the material composition. Thus, it is possible to describe the influence of relative humidity onto the load-bearing behaviour of unstabilised earth masonry materials in a generally valid formulation.